Dysregulation of TLR2 Serves as a Prognostic Biomarker in Breast Cancer and Predicts Resistance to Endocrine Therapy in the Luminal B Subtype - Wang, Yunmei; Liu, Shuguang; Zhang, Yanjun; Yang, Jin (Frontiers in Oncology, 2020)
Abstract Background: Breast cancer (BCa) is a serious global healthy burden among females and the increasing endocrine resistance becomes a major BCa treatment challenge. This study aimed to investigate the expression of Toll-like receptor 2 (TLR2) in BCa patients, and evaluate the prognostic value of TLR2 and its predictive potential for the endocrine resistance. Methods: A total of 150 BCa patients were recruited in this study, including 82 cases underwent endocrine therapy. Expression of TLR2 mRNA was examined using quantitative Real-Time PCR, and its prognostic value was evaluated using Kaplan-Meier survival analysis. The expression changes of TLR2 in BCa patients with endocrine resistance was assessed and the predictive value of TLR2 for endocrine resistance was evaluated using a receiver operating characteristic curve analysis. Results: Expression of TLR2 was elevated in BCa tissues compared with the normal tissues and associated with patients’ tumor size, HER2 status, subtypes and TNM stage. The upregulation of TLR2 could predict a poor prognosis of BCa. In addition, an increased expression of TLR2 was observed in the BCa patients with endocrine resistance, and this increase was more obviously in the HER2-positive BCa cases. The predictive performance of TLR2 for endocrine resistance was relatively high in HER2-positive BCa cases compared with the other BCa cases with positive hormone receptor. Conclusion: All the data indicated that the elevated TLR2 serves as a promising biomarker for the prognosis and resistance of endocrine therapy. The relationship between TLR2 and HER2 indicates that TLR2 may be involved in endocrine resistance through the HER2 signaling in BCa